A Pathologically Abnormal Situation: Le Cercle Gaston Crémieux and the [Im]Possibility of an Anti-National Jewishness - Swanson, Joel Howard (Religions, 2022)
This paper examines the diasporist French Jewish political group, Le Cercle Gaston Crémieux, founded in 1967 “to promote a diasporic Jewish existence without subjugation to the synagogue or to Zionism”. In contrast to either an assimilationist model which demanded the acceptance of French national identity in the public sphere, or a Zionist model of Jewish nationalism, the Cercle offered a model in which the state of exile and diaspora becomes constitutive of Jewish identity, positioned as an alternate mode of being-in-the-world defined against white Christian European nationalism. Yet to expose the historically constructed, socially contingent nature of European nationalisms that claim the status of organic and natural, the Cercle had to imagine a particular narrative of the historical construction of Jewishness, and this social constructionism conflicted with the almost ontological, metaphysical status they wanted to accord to Jewish exile and otherness. Thus the Cercle failed to imagine an anti-national model of Jewishness, but this failure sheds light on larger fault lines in the possibility of a Jewish politics. The paper concludes that the Cercle’s imaginal diasporic Jewishness tries to enable the articulation of other forms of minority identity, suggesting that this failure may nonetheless prove politically productive.